Optimization of fuzzy entropy on solar panel’s motor - MUHAMMAD IKHWAN; MARWAN RAMLI; MARDLIJAH MARDLIJAH (Universitas Syiah Kuala, 2022)
Renewable energy has been in great demand by the public, even some countries have set regulations for substitution and transition from fossil energy to renewable energy. This study aims to modify the fuzzy control system with a metaheuristic method, namely fuzzy entropy. The entropy value of the fuzzy set in the previous stage becomes the basis for calculating the foot of uncertainty in the new fuzzy set. This process makes the entropy method parallel to other optimization methods that have been carried out on fuzzy control systems. The results obtained indicate that the modified fuzzy control system successfully controls the angle and angular velocity of the solar panel. The error value shown is very small and the time to reach stability is below 5 s. This is a rapid development of several previous studies. The modified system has no overshoot and steady state error below 1%. Based on these results, entropy research can be developed again by changing the fuzzy set to a more complex form.